Evaluasi Kontaminasi Penambangan Batubara Seam E PT Bumi Merapi Energi Blok Kungkilan di Kabupaten Lahat - Arisanti, Reni; Salfitri, Aisyah; Susilo, Aris (Green Publisher Indonesia, 2024)
PT Bumi Merapi Energi is a company engaged in coal mining which is administratively located in Muara Maung Village, West Merapi District, Lahat Regency, South Sumatra Province. This research was carried out in the Kungkilan block in the Seam E area, where all mining activities are carried out by parties. second (contractor), namely by PT Ansaf Inti Resources using the open mining method. So there are several factors that cause contamination, one of which is contamination from within in the form of clay/clay material so it needs to be handled using the parting and cleaning separation method using a PC200 Excavator and it must be in accordance with the company's coal getting SOP, namely if it is above 10cm then cleaning is carried out and if it is below 10cm coal getting is carried out directly at the same time as the coal so that the quality of the coal does not decrease too far.